The Effect of Variable Valve Timing on Spark Ignition Engine Performance and its Emissions using Ricardo Wave program (Damascus University Journal for engineering sciences, 2024)
The modern automotive Internal Combustion Engines (ICEs) are characterized by more and more complex architectures in order to minimizethe fuel consumption, without penalizing power and torque performance, and to comply with the European law concerning the pollutants and CO2 emissions.The present work deals with the open, close and overlap period variation effects on spark ignition engine performance; by changing the intake and exhausts valves open and close timings in Ricardo wave software.  The study focuses on the impact of this timing variation on engine performance, Brake specific fuel consumption and exhaust gases emission. The work was conducted on single cylinder engine SI engine type
Keywords: Variable valve timing; overlap period; engine performance, emissions; spark ignition engines; Volumetric Efficiency; BSFC Brake specific fuel consumption; engine speed; Power; Torque